Evaluation of the potential of supplements to substitute for range forage - S.D. Stafford; R.C. Cochran; E.S. Vanzant; J.O. Fritz (Kansas Agricultural Experiment Station Research Reports, 1994)
Thirteen, ruminally fistulated, Angus x Hereford, yearling steers were used to evaluate the effect of feeding different types and amounts of supplements on t h e likelihood of observing a substitution of supplement for range forage. Steers had ad libitum access to low-quality range forage and were fed a supplement comprised of sorghum grain (SG) and soybean meal (SBM ) that contained 18% CP (SG/SBM 18%), a SG/SBM supplement that contained 36% CP (SG/SBM 36%), long-stem alfalfa hay (18% CP), or alfalfa-pellets (18% CP) in amounts that provided .05, .10, and .15 % BW o f CP/day. In general, supplementation increase d the intake and digestibility of low-quality range forage. No substitution effect was observed for the SG/SBM 36% supplement or the alfalfa pellets. However, the SG/SBM 18% supplement did substitute for forage at the high level of supplementation. A similar trend appeared to exist for the long-stem alfalfa hay.
Keywords: Cattlemen' s Day; 1994; Kansas Agricultural Experiment Station contribution; no. 94-373-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 704; Beef; Supplementation; Alfalfa; Range forage; Pellets